Gambaran Gangguan Mental Emosional pada Pasien Kanker Payudara Post Mastektomi di RSUD Arifin Achmad - Azimah, Azimah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Mental emotional disorders are psychological problemse xperienced by post-mastectomy breast cancer patients. This study aims to identify the description of mental emotional disorders in post-mastectomy breastc ancer patients at Arifin Achmad Hospital. This study usedd escriptive research design. The sample in this study were 55 respondents witht otal sampling technique. The measuring instrument used is Self ReportQ uestionnaire 20 (SRQ-20). The analysis used was univariate descriptivea nalysis. The results of univariate analysis showed that mostr espondents were in the early elderly age range of 46-55 years (50,9%), mostr espondents last education was high school (32,7%), the majority of respondentso ccupations were housewife (80%), most respondents marital status was married (96,4%), most respondents post mastectomy duration was 4-6 months (72,7%),m ost respondents mastectomy type was radical mastectomy + dissection( 56,4%), most respondents therapy type was mastectomy + chemotherapy( 56,4%), this study also showed that more than half of post mastectomy breast cancer patients experienced mental emotional disorders (65,5%). The results of this study show that most post-mastectomy breast cancer patientse xperience mental emotional disorders.